2020
DOI: 10.1007/s42864-020-00039-5
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of radiation-induced defects with tungsten grain boundaries at across scales: a short review

Abstract: As promising candidates for plasma-facing materials, tungsten-based materials suffer the irradiation of high-energy neutrons in addition to the hydrogen isotopes and helium irradiation and the high-thermal flux. Radiation-produced defects, e.g. selfinterstitial atoms (SIAs) and vacancies (Vs), can induce the hardening and embrittlement of tungsten, meanwhile enhancing the retention of hydrogen isotopes and helium in tungsten. Reducing the grain size of materials to introduce a high density of defect sinks, e.g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 60 publications
2
1
0
Order By: Relevance
“…The trend in the number of interstitials at the stabilization stage aligned with the Norgett–Robinson–Torrens (NRT) model [ 42 ]. All these results are consistent with observations from other studies [ 31 , 35 , 43 , 44 ].…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…The trend in the number of interstitials at the stabilization stage aligned with the Norgett–Robinson–Torrens (NRT) model [ 42 ]. All these results are consistent with observations from other studies [ 31 , 35 , 43 , 44 ].…”
Section: Resultssupporting
confidence: 94%
“…The trend in the number of interstitials at the stabilization stage aligned with the Norgett-Robinson-Torrens (NRT) model [42]. All these results are consistent with observations from other studies [31,35,43,44]. To gain a comprehensive understanding of the influence of the PKA energy on the irradiation damage, the defect clustering and distributions at different moments are shown in Figure 5.…”
Section: H Concentration Effect On Displacement Damagesupporting
confidence: 87%
“…Controlling the grain morphology during the fabrication process is a conventional way to improve the thermodynamics and mechanical properties of materials. Previous work has revealed that grain boundaries (GBs) can serve as sinks for defects to improve the irradiation resistance by reducing the formation energy of defects and the diffusion barrier at GBs [18][19][20][21], but also impede the heat transfer across them [22,23]. During the service, the combination of high temperature and high energy neutron irradiation can promote the GB migration and lead to grain growth [24][25][26][27], that is, the small grains with relatively large curvatures decrease their sizes, resulting in the increased overall average grain size.…”
Section: Introductionmentioning
confidence: 99%